Pumpkinhead [videorecording (DVD)] - Winston, Stan, 1946-2008; Henriksen, Lance, 1940-; DiAquino, John, 1958-; Shauffler, Florence (MGM Home Entertainment, 2008)
In a backwoods community, a father tries to avenge the death of his child by evoking the vengeful demon named Pumpkinhead.